First Year Learning Experiences of University Undergraduates in the Use of Open Educational Resources in Online Learning - Afolabi, Folashade (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
This study investigated -the first year University undergraduates’ experiences in the use of open educational resources (OER) in online learning and their in-course achievement. The design selected for the study was survey and quasi-experimental. A total number of 106 University undergraduates participated in the study after a preliminary study was conducted to ascertain undergraduates’ perception and acceptability of OER. A structured questionnaire on 4-point Likert scale and Achievement Test were used to collect data. The two instruments were validated and trial tested to established reliability using Cronbach’s alpha.  Data were analysed using simple percentage and t-test. The results clearly shown that understanding of online learners’ skills, acceptability, perception, and competencies is necessary to provide intervention strategy and appropriate support service which could facilitate their understanding and learning of difficult concepts.  It was also discovered that that students that have positive perception of OER performed very well in the achievement test administered.